(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
Medical education privatization can increase its breadth and usability by producing a set of osteopathic medical professionals for Indians, so how can it be a replacement to building capacity with the expertise and skill mix, particularly when services are needed? Involving human lives require urgent rethinking? The goal of this study is to look at the problems surrounding the privatization of India’s medical education system. Materials and Procedures: Since the past 20 years, a systematic evaluation of major indexed journals of key medical search engines, such as Pub med, Here on primary search words "Corporatization of Health Schooling," we searched Lancet, Microbe Online, and Google Scholar in all forms, including u t. India ranks 67th out from 133 underdeveloped countries in a WHO survey, with just a pediatrician proportion of 1:1700, contrasted to a nationwide average of 1.5:1000. That is to say, despite over than fifty years of freedom, not a single doctor is available for every 1000 people; a goal that is still a long way off, according to the Bhore committee’s recommendation in 1946, which was later modified by the Mudaliar committee in 1961 and the Bajaj committee in 1987.